Bullets and bolos fifteen years in the Philippine Islands - White, John Roberts 1879- (The Century Co. Felta Multi-Media Center, 2008)
"The account of thirteen years in the Philippine constabulary by one who was one of its most gallant and outstanding officers."--Foreword.